2013
DOI: 10.5539/ass.v9n3p182
|View full text |Cite
|
Sign up to set email alerts
|

Safety Culture in Combating Occupational Safety and Health Problems in the Malaysian Manufacturing Sectors

Abstract: Rapid economic growth via industrialization has given not only a significant impact in terms of income distributions and quality of life, but it also resulted in increasing number of accidents at workplace. In reducing risk at the workplace, Occupational Safety and Health (OSH) is an important aspect. It is a standard which are set in legislation with the aim to eliminate and reduce hazards at workplace. Besides OSH, the term of 'safety culture' is also an important aspect in reducing risk and accident at work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Based on this, it can be concluded that safety culture can be developed, formed, or created in accordance with the goals and characteristics of the company. According to the previous study said that in the development of safety culture needed to pay attention to several things that the measurement of safety behavior, observation of worker's readiness, observation of work environment condition, and management commitment 18 . Besides that, development is done by various ways, for example through the leadership approach, Behavioral Based Safety (BBS) program, integration of OSH management system, improves supervision and etc 16 .…”
Section: Safety Culture Of Weldersmentioning
confidence: 99%
“…Based on this, it can be concluded that safety culture can be developed, formed, or created in accordance with the goals and characteristics of the company. According to the previous study said that in the development of safety culture needed to pay attention to several things that the measurement of safety behavior, observation of worker's readiness, observation of work environment condition, and management commitment 18 . Besides that, development is done by various ways, for example through the leadership approach, Behavioral Based Safety (BBS) program, integration of OSH management system, improves supervision and etc 16 .…”
Section: Safety Culture Of Weldersmentioning
confidence: 99%
“…This could be seen in the construction industry, aviation, maritime, medical sector and road transport to name a few (Reiman and Rollenhagen, 2014). Presently, safety culture at the workplace had been recognised as one of the foremost contributing factors to near misses, accidents and injuries (Amirah et al, 2013). Therefore, it is the sole responsibility of the organisation to foster positive workplace safety culture through a good communicative mechanism system so that there are minimal workplace injuries and other related mishaps.…”
Section: E Cultural Barriersmentioning
confidence: 99%
“…Smoking as a stimulant, to experience the positive affect of great enthusiasm, and smoking as a relaxant, to experience the positive affect of enjoyment [24]. The latter occurs in those individuals who characteristically smoke under pleasant circumstances which are relaxing such as at the end of a meal, or in the midst of a pleasant conversation [25]. The stimulant type of smoking occurs whenever smoking is used to give the person a rise from the positive affect of great enthusiasm as when an adolescent smokes to establish his manhood or his coming of age, or to against his parents, or when an adult smokes for the great enthusiasm of something to do.…”
Section: Fig 1: Boxplots Of Perception Score For Smoking Factors Relmentioning
confidence: 99%